Humanitarian intervention : ideas in action - Weiss, Thomas George; Evans, Gareth J., 1944- (Cambridge : Polity Press, 2012)
A singular development of the post Cold-War era is the use of military force to protect human beings. From Rwanda to Kosovo, Sierra Leone to East Timor, soldiers have rescued civilians in some of the world's most notorious war zones. Drawing on two decades of research, the author provides an introduction to the theory and practice of humanitarian intervention in the modern world. He examines political, ethical, legal, strategic, economic, and operational dimensions and uses a wide range of cases to highlight key debates and controversies. This survey is neither celebratory nor complacent. The author locates the normative evolution of what is increasingly known as'the responsibility to protect' in the context of the war on terror and the 2005 UN World Summit. The result is an exploration of the current dilemmas and future challenges for international humanitarian action in the 21st Century.
Conceptual building blocks --'Humanitarian' interventions: thumbnail sketches -- New wars and new humanitarianisms -- New thinking: the responsibility to protect -- So what? : Moving from rhetoric to reality.
Includes bibliographical references and index.
Keywords: Humanitarian intervention; Intervention (International law).